2014
DOI: 10.1080/14786419.2014.958736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seasonal chemical composition, antibacterial, antioxidant and anticholinesterase activity of essential oil fromEugenia brasiliensisLam.

Abstract: This study describes the seasonal composition and the antibacterial, antioxidant and anticholinesterase activity of the essential oil from Eugenia brasiliensis leaves. Analysis by using GC allowed the identification of 40 compounds. It was observed that the monoterpenes varied more (42%) than the sesquiterpenes (14%), and that the monoterpene hydrocarbons suffered the greatest variation throughout the year (64%). Major compounds were spathulenol in the spring (16.02 ± 0.44%) and summer (18.17 ± 0.41%), τ-cadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
0
18
4
Order By: Relevance
“…That is contrary to what was generally described for Eugenia EOs in the literature ( Lima et al 2008;Siebert et al 2015).…”
Section: Seasonal Chemical Compositioncontrasting
confidence: 80%
See 2 more Smart Citations
“…That is contrary to what was generally described for Eugenia EOs in the literature ( Lima et al 2008;Siebert et al 2015).…”
Section: Seasonal Chemical Compositioncontrasting
confidence: 80%
“…These results were more promising than those of previous reports in the literature with EOs from the leaves of E. brasiliensis (Siebert et al 2015) and Thyme vulgaris (Arjoon et al 2012). …”
Section: Antimycoplasmic Activitycontrasting
confidence: 43%
See 1 more Smart Citation
“…Essential oils (EO), concentrated hydrophobic liquids, containing volatile aromatic compounds such as terpenes and phenols, represent examples of them. Based on the cyclical system of conjugated double bonds in the molecule of the compound, spatial arrangement and the various substituents it can be assumed that many of EO manifest antioxidant properties [37][38][39]. A great advantage of EO is that they are able to penetrate into a tissue up to 100-times faster than water [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies has showed the biomedical potentials of oils from Eugenia plants (Ogunwande et al, 2005;Siebert et al, 2015), including antifertility activities for Eugenia jambolana (Rajasekaran et al, 1988). Similarly, the presence of β-caryophyllene, a chemical component identified in Eugenia brejoensis, has been reported in the oil of Trachyspermum ammi which also has spermicidal action (Paul and Kang, 2011).…”
Section: Resultsmentioning
confidence: 99%